2008
DOI: 10.1889/1.3069371
|View full text |Cite
|
Sign up to set email alerts
|

P‐28: ZnO TFTs Fabricated at Room Temperature by Solution Process

Abstract: The ZnO nanorods TFT using solution process was investigated. The nanorods were well‐chemically synthesized by ultrasonic methods and their length and diameter were adjusted to about 50∼150nm and 5∼15nm, respectively. The nanorods were coated onto SiO2 substrate by spin casting. The nanorods films were treated at room temperature condition. The device exhibits an on‐to‐off current ratio of 8.6 × 105 and a field mobility 2.1 cm2V−1s−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The approaches based on ZnO nanoparticles have also shown a potential for low temperatures below 230°C and even to room temperature. [27][28][29][30] As a material-based approach, Schneider et al 31 reported a synthesized Zn precursor for the low-temperature process. They obtained a mobility of 1.02×10 -3 cm 2 /Vsec by calcination of printed ZnO at 150°C.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches based on ZnO nanoparticles have also shown a potential for low temperatures below 230°C and even to room temperature. [27][28][29][30] As a material-based approach, Schneider et al 31 reported a synthesized Zn precursor for the low-temperature process. They obtained a mobility of 1.02×10 -3 cm 2 /Vsec by calcination of printed ZnO at 150°C.…”
Section: Introductionmentioning
confidence: 99%
“…The development of electronic and optoelectronic devices attending the increasing demand of new features like high-resolution, fast response, transparency and flexibility has motivated the pursuit of circuits using new active materials and/or new processing technologies. In this sense, semiconducting metal oxides (SMOs) as zinc oxide (ZnO) [1][2][3][4][5][6][7][8][9] and related compounds like aluminumdoped zinc oxide (AZO) [10][11][12][13], indium zinc oxide (IZO) [14,15] and indium gallium zinc oxide (IGZO) [16,17] are promising materials for flexible, transparent and high-performance electronics.…”
Section: Introductionmentioning
confidence: 99%
“…SMOs are particularly interesting to be used as the active layer of thin-film transistors (TFTs), which constitute the basic electronic device for drive circuits of active-matrix displays (AMDs) and more sophisticated logic circuits which can be used in memories, microcontrollers and processors. Recently, the manufacture of metal oxide thin films using organic precursor solutions or nanoparticle suspensions became widespread [1][2][3][4][5][6][7][8][9][10], permitting the use of low-cost and nonsophisticated deposition techniques as spin coating, ink-jet printing and spray pyrolysis [18][19][20][21]. These techniques produce very uniform and homogeneous nanoscaled films, with high control of thickness and of other physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with poly-Si, TOS is considered to have better uniformity and therefore is easier to be applied on larger glass substrates (>Gen. 5) and OLED applications. Because TOS can be prepared by pulse laser deposition (PLD) [1], sputtering [2], or solution-process [3], the process temperature is much lower than that of the amorphous silicon, which is generally prepared by PECVD at the temperature above 300 °C. This advances the usage of TOS TFTs on temperature-sensitive plastic substrates and flexible applications.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been made in developing suitable TOS materials and lots of candidates, such as ZnO [3,4], IZO [5], ITO [2], a-IGZO [1,6,7], and ATZO [8], have been investigated. Among various techniques for active layer preparation, sputtering is preferred for commercialization due mainly to its throughput, stability, and technical maturity.…”
Section: Introductionmentioning
confidence: 99%